Strength distributions of laminated FeNi-based metal amorphous nanocomposite ribbons. (April 2023) - Schneider, Kyle P; McHenry, Michael E; de Boer, Maarten P
Metal Amorphous Nanocomposite (MANC) materials offer low losses at high magnetic switching frequency, enabling high power density motors with increased rotational speed. While MANCs have high strength, they are brittle. The use of motor components such as a rotor consisting of brittle material presents a reliability concern. Here, a promising MANC alloy is subjected to tensile tests and failure is observed with high-speed photography. A method is developed to prepare tensile specimens of laminated MANC and epoxy layers, simulating the stacking of an epoxy-impregnated tape-wound core. Tensile tests are conducted for single layer ribbon and for five- and ten-layer stacks of laminated material with thin layers of thermosetting epoxy. Failure distributions are shown to have increasing Weibull modulus with increasing layer count. The composite MANC material system is modeled using chain-of-bundles models. Using a k-failure model, we show that single ribbon strength distribution data can be used to predict well the failure distribution of laminated stacks. The agreement occurs when the assumed ineffective length, over which load is recovered in a failed layer, is comparable to the observed interlaminar separation length.